PICTURE OF THE LEVEL KNOWLEDGE MOTHER ABOUT EDUCATION GAMES OF PRESCHOOL CHILDREN IN KINDERGARTEN AISYIYAH KARANGGAYAM SUMBER SIMO BOYOLALI - Mar’ah, Sarifatul; ., Sugihartiningsih (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
Education games is a game tool that can provide an optimal games functions and development of the children, where the children through it will always be able to develop their physical abilities, language, cognitive abilities, and social adaptation. The results of a preliminary study conducted in Kindergarten Aisyiyah Karanggayam Sumber Simo Boyolali about knowledge of mothers about education games for preschool children. From interviewing 8 mothers, founded 2 mothers knew nothing about education games, 3 mothers knew about education games, and 3 mothers hesitated when expressing types of educational games. The purpose of this study is to know the picture of the level of motherâs knowledge about education games of preschool children in Kindergarten Aisyiyah Karanggayam Sumber Simo Boyolali. This research was descriptive. The population in this research was all mothers had children school in Kindergarten Aisyiyah Karanggayam Sumber Simo Boyolali. The sample method was total sampling. The instrumen used questionnaire that identify the name, age, education, job, and question knowledge about education games. The results showed based on age can be the most dominant are in the age range 27-35 years as many as 20 respondents (66.7%). Mothers knowledge of educational games in preschool children most of the respondents have a good level of knowledge (60%), sufficient (30%), and less (10%). The conclusions in this study is knowledge of mother about education games for preschool children in Kindergarten Aisyiyah Karanggayam Sumber Simo Boyolali was good that percentage 60%. Â  Keywords: Knowledge, Education games